2022
DOI: 10.3389/fphar.2022.1066244
|View full text |Cite
|
Sign up to set email alerts
|

Fuzheng Nizeng Decoction regulated ferroptosis and endoplasmic reticulum stress in the treatment of gastric precancerous lesions: A mechanistic study based on metabolomics coupled with transcriptomics

Abstract: Background: Fuzheng Nizeng Decoction (FZNZ) has a history of decades in gastric precancerous lesions (GPL) treatment, which has shown clear clinical efficacy. Blocking GPL is a key measure to reduce the incidence of gastric cancer (GC). Therefore, we aim to investigate the mechanism of FZNZ-induced ferroptosis and endoplasmic reticulum (ER) in MNNG-induced gastric precancerous lesion (MC) cells, which has been rarely studied in Traditional Chinese Medicine (TCM).Methods: First, CCK8 and lactate dehydrogenase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Studies have found that herbal medicine for GC may be associated with ER stress pathway activation [ 15 , 35 ]. Ferroptosis and ER stress could be brought on by Fuzheng Nizeng Decoction [ 36 ]. Small molecules from traditional Chinese medicine are able to activate ER stress to exert anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that herbal medicine for GC may be associated with ER stress pathway activation [ 15 , 35 ]. Ferroptosis and ER stress could be brought on by Fuzheng Nizeng Decoction [ 36 ]. Small molecules from traditional Chinese medicine are able to activate ER stress to exert anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a distinct form of cell death that relies on iron-dependent lipid peroxidation, distinguishing it from apoptosis, autophagy, and necrosis [ 16 ]. Ferroptosis has been observed in both inflammatory bowel disease (IBD) and GC [ 25 , 26 ]. The antitumor effects of ferroptosis have been demonstrated, but it can also promote tumor growth and survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As revealed by IHC assay, JYQHD group displayed the reduced levels of COL12A1, GPX4 and SLC7A11, while an elevated levels of COL12A1, GPX4 and SLC7A11 were shown in JYQHD + oe-COL12A1 group. A previous study elaborated that Fuzheng Nizeng Decoction regulated ferroptosis and endoplasmic reticulum stress in the treatment of gastric precancerous lesions [ 84 ]. Our consequences presented that JYQHD activated the ferroptosis and inhibited the stemness in GC cell lines.…”
Section: Discussionmentioning
confidence: 99%